Complete ligand loss in electron ionization of the weakly bound organometallic tungsten hexacarbonyl dimer. Issue 15 (23rd March 2016) - Neustetter, Michael; Mauracher, Andreas; Limão-Vieira, Paulo; Denifl, Stephan
Abstract : Electron ionization of the weakly bound tungsten hexacarbonyl dimer leads to a transformation of the weak intermolecular bond into a strong valence bond. Abstract : We observed the bare W2 + metal cation upon electron ionization of the weakly bound W(CO)6 dimer. This metal cation can be only observed due to the fast conversion of the weak cluster bond into a strong covalent bond between the metal moieties.